Difference analysis of intestinal microbiota and metabolites in piglets of different breeds exposed to porcine epidemic diarrhea virus infection - Li, Zhili; Zhang, Wandi; Su, Langju; Huang, Zongyang; Zhang, Weichao; Ma, Liangliang; Sun, Jingshuai; Guo, Jinyue; Wen, Feng; Mei, Kun; El-Ashram, Saeed; Huang, Shujian; et al. (Frontiers in Microbiology, 2022)
The gut microbial composition of the Luchuan (LC) piglet, one of China's native breeds, has rarely been studied, especially when compared to other breeds. This study constructed artificial infection models of PEDV in LC and Largewhite (LW) piglets, and analyzed the patterns and differences of intestinal microbial communities and metabolites in piglets of these two breeds after infection. The diarrhea score, survival time, and distribution of viral antigens in the intestine of piglets infected with PEDV differed among breeds, with the jejunal immunohistochemistry score of LW piglets being significantly higher than that of LC piglets (P < 0.001). The results of 16S rRNA sequencing showed differences in microbial diversity and community composition in the intestine of piglets with different breeds between PEDV infection piglets and the healthy controls. There were differences in the species and number of dominant phyla and dominant genera in the same intestinal segment. The relative abundance of Shigella in the jejunum of LC piglets after PEDV infection was significantly lower than that of LW piglets (P< 0.05). The key microorganisms screened for structural differences in the microbiota were Streptococcus_alactolyticus, Roseburia_faecis, Lactobacillus_iners, Streptococcus_equi and Lactobacillus_mucosae (P < 0.05). The non-targeted metabolite analysis revealed that intestinal metabolites showed great differences among the different breeds related to infection. After that, Spearman correlation analysis was conducted to see any links between the microbiota and metabolites. The metabolites in the intestine of different breeds related to infection were mainly involved in arginine biosynthesis, synaptic vesicle cycle, nicotinic acid and nicotinamide metabolism and mTOR signaling pathway, with significant positive or negative correlations (P<0.05) between the various screened microorganisms. This study provides ideas and a theoretical foundation for investigating the application of core microorganisms in the gut of piglets of different breeds in the digestive tracts of those infected with PEDV, and helps to tackle the antimicrobial resistance problem further.